Ο ΧΡΥΣΑΝΘΟΣ ΝΟΤΑΡΑΣ ΚΑΙ Η ΕΚΔΟΣΗ ΤΗΣ «ΔΩΔΕΚΑΒΙΒΛΟΥ» ΤΟΥ ΔΟΣΙΘΕΟΥ ΙΕΡΟΣΟΛΥΜΩΝ: ΜΙΑ ΠΕΡΙΠΤΩΣΗ ΑΝΑΛΗΘΟΥΣ ΧΡΟΝΟΛΟΓΙΑΣ ΕΚΔΟΣΗΣ (1715 / c.1722) - ΣΑΡΡΗΣ, ΚΩΣΤΑΣ (Μνήμων, 2005)
Kostas Sarris, Chrysanthos Notar as and the publication of "Dodekavivlos" by Dositheos of Jerusalem: a case of false publication date (1715 / c.1722) The article focuses on «Dodekavivlos» by Dositheos the patriarch of Jerusalem (1641-1707). His historiographic work was published after his decease by the Greek publishing house of Anthime in Bucharest. The book was edited by his nephew and successor to the patriarchical throne of Jerusalem Chrysanthos Notaras and the publisher and future bishop of Wallachia Mitrofanis Grigoras. The study concentrates on the false date of publication noted under the title of "Dodekavivlos", that is to say, October 1715, whereas, in reality, the book was published between 1721 and 1723. In the first part of the article, the process followed during the edition and the publication of the book is depicted. Moreover, the outset of the aforementioned procedure as well as the publication date of «Dodekavivlos» is determined. In this context, some aspects of history of the publishing house Anthime are clarified whilst the publishing work and the technical impediments confronted by a Greek publishing house in the Rumanian Principalities in the turning point of the 18th century are delineated. The second part of the article attempts to formulate a cohesive and comprehensive interpretation of the false publication date. Both the polemic character of the content of «Dodekavivlos», which due to the rivalry over the religious establishments of the Holy Land, was of political nature, and Chrysanthos Notaras' correspondence along with the historical background of the publication can conduce to some conjectures over Chrysanthos' decision not to record the real date but an earlier one as well as the choice of the particular date of the title. According to the interpretation brought forward, Nicolaos Mavrokordatos' potential political ventures played a significant role. Also, telltale, though of less importance, is the fact that the name of the publisher and bishop of Wallachia Anthimos Iviritis is not recorded under the false date of the title of «Dodekavivlos».